2017
DOI: 10.1186/s12884-017-1542-y
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal ectopic pregnancy: a case report and review of the literature

Abstract: BackgroundRetroperitoneal ectopic pregnancy (REP) is an extremely rare type of ectopic pregnancy, with a total of less than 20 cases reported in the English literature. However, failure to recognize REP may result in severe consequences.Case presentationWe report a case of 32-year-old woman with REP. She had amenorrhea, left lower abdominal pain, but no vaginal bleeding. Her urine human chorionic gonadotropin (HCG) test was positive and blood HCG level was 1880 m-international units per milliliter (mIU/mL). Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Ectopic pregnancy is defined as the implantation of the fertilized egg outside the endometrial cavity of the uterus. It occurs in 2% of all pregnancies, with 95% of the cases occurring in the fallopian tube [1]. Abdominal pregnancy is a rare type of ectopic pregnancy, with a reported 1 , 2 3 3 3, 4 Open Access Case Report DOI: 10.7759/cureus.8276 incidence of 1:10,000 to 1:30,000 pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic pregnancy is defined as the implantation of the fertilized egg outside the endometrial cavity of the uterus. It occurs in 2% of all pregnancies, with 95% of the cases occurring in the fallopian tube [1]. Abdominal pregnancy is a rare type of ectopic pregnancy, with a reported 1 , 2 3 3 3, 4 Open Access Case Report DOI: 10.7759/cureus.8276 incidence of 1:10,000 to 1:30,000 pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in 2% of all pregnancies, with 95% of the cases occurring in the fallopian tube [1]. Abdominal pregnancy is a rare type of ectopic pregnancy, with a reported 1 , 2 3 3 3, 4 Open Access Case Report DOI: 10.7759/cureus.8276 incidence of 1:10,000 to 1:30,000 pregnancies [2]. It could be life-threatening with maternal mortality eight times greater than the usual tubal ectopic pregnancies [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of retroperitoneal ectopic pregnancy is still unclear. Some scholars have shown that it may be caused by the following reasons 1) active embryonic villi may enter the retroperitoneum after fallopian tube injured or ruptured and invaded blood vessels and causing hematoma 2) the fertilized egg travels through the lymphatic system to the retroperitoneal space, similar to the lymphatic metastasis of malignant tumors 3) a fistula is formed between the end of the fallopian tube and the retroperitoneum after salpingectomy, so that the uterus is directly identical to the retroperitoneum [2,10,11]. The diagnosis of retroperitoneal ectopic pregnancy should be differentiated from diseases such as retroperitoneal mass and traumatic hematoma.…”
Section: Disscussionmentioning
confidence: 99%
“…Lokalizasyon bakımından, EG'lerin %95'inin tubal, %1,4'ünün abdominal ve %1' den daha azının da servikal ya da ovaryan yerleşimli olduğu belirtilmiştir (11). Bunlar dışında, daha az sıklıkta splenik bölgede ve sezaryen kesi bölgesinde de EG görülebilmektedir (5,12,13). Anatomik veya fonksiyonel tubal tıkanıklık, bozulmuş tubal hareketlilik, siliyer fonksiyonda bozulma ve tüp implantasyonunu uyaran veya destekleyen moleküler kemotaktik faktörler, EG gelişiminde öne sürülen mekanizmalardandır (5).…”
Section: Introductionunclassified